Cold Hardiness and Supercooling Capacity in the Overwintering Larvae of the Codling Moth, Cydia pomonella - Khani, Abbas (University of Wisconsin Library, 2010)

(untitled)
The codling moth, Cydia pomonella L. (Lepidoptera: Tortricidae), a worldwide apple pest, is classified as a freeze-intolerant organism and one of the most cold-tolerant pests. The objectives of this study were to examine the supercooling point of overwintering and non-diapausing larvae of C. pomonella as an index of its cold hardiness, and to assess larval mortality following 24 h exposure to extreme low temperatures ranging from -5 to -25°C. The mean (±SE) supercooling point for feeding larvae (third through fifth instars) was -12.4 ± 1.1°C. The mean supercooling point for cocooned, non-diapausing larvae (i.e., non-feeding stages) decreased as the days that the arvae were cocooned increased and changed between -15.1 ± 1.2°C for one to two day cocooned arvae and -19.2 ± 1.8°C for less than five day cocooned larvae. The mean (±SE) supercooling point for other non-feeding stages containing pupae and overwintering larvae were -19.9 ± 1.0°C and -20.2 ± 0.2°C, respectively. Mean supercooling points of C. pomonella larvae were significantly lower during the winter months than the summer months, and sex had no effect on the supercooling point of C. pomonella larvae. The mortality of larvae increased significantly after individuals were exposed to temperatures below the mean supercooling point of the population. The supercooling point was a good predictor of cold hardiness.